1985
DOI: 10.1099/0022-1317-66-10-2089
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal Antibody-based Biotin-Avidin ELISA for the Detection of Soybean Mosaic Virus in Soybean Seeds

Abstract: SUMMARYTwo monoclonal antibodies (M-Ab) specific for different epitopes on particles of soybean mosaic virus (SMV) were used in a double-antibody sandwich ELISA (M-Ab ELISA). The non-isotopic immunoassay, which used a biotinylated second antibody and an avidin-alkaline phosphatase detection system to detect SMV in soybean seed extracts, was compared with a polyclonal antibody-based solid-phase radioimmunoassay (SPRIA). M-Ab ELISA detected less than l0 ng of SMV/ml and was more sensitive than the SPRIA which de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…For all immunological assays, a biotin-avidin double antibody sandwich enzyme-linked immunosorbent assay (ELISA) was used. The ELISA was similar to that described previously (Diaco et al 1985), except that wells of Immulon 1B polystyrene microtiter plates (Dynex Technologies Inc., Chantilly, VA) were coated with anti-BPMV polyclonal antibody prepared to the I-JH1 BPMV isolate (Gu et al, 2002) (1.0 g/ml) and biotinylated polyclonal anti-BPMV was used at 0.5 g/ml. Alkaline-phosphatase conjugated extravidin (1:40,000) (Sigma-Aldrich, St. Louis, MO) was followed by p-nitrophenyl phosphate (1 mg/ml).…”
Section: Fieldmentioning
confidence: 99%
“…For all immunological assays, a biotin-avidin double antibody sandwich enzyme-linked immunosorbent assay (ELISA) was used. The ELISA was similar to that described previously (Diaco et al 1985), except that wells of Immulon 1B polystyrene microtiter plates (Dynex Technologies Inc., Chantilly, VA) were coated with anti-BPMV polyclonal antibody prepared to the I-JH1 BPMV isolate (Gu et al, 2002) (1.0 g/ml) and biotinylated polyclonal anti-BPMV was used at 0.5 g/ml. Alkaline-phosphatase conjugated extravidin (1:40,000) (Sigma-Aldrich, St. Louis, MO) was followed by p-nitrophenyl phosphate (1 mg/ml).…”
Section: Fieldmentioning
confidence: 99%
“…15, 3436 The incorporation of a biotin tag can be used for lectin-sugar interaction studies using avidin affinity chromatography and/or avidin coated micro-well plates. 37, 38 Functionalization of N-linked glycans with 5-carboxyfluorescein introduces a fluorescent chromophore 9 that can be used in many types of fluorescence experiments. On-resin labeling was achieved by using 10 equivalents of each of the previously specified functional labels, 10 equivalents of DEPBT, and 5 equivalents of DIEA.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies, using several diverse antigens, have suggested that modification of the standard double-sandwich enzyme-linked immunosorbent assay (ELISA) may provide enhanced detection that can be used for plant viruses (KONI]N et al 1982, NEURATH and STRICK 1981, SHALEV et al 1980, TORRANCE and JONES 1982, YOLKEN and STOPA 1979. It has been demonstrated that enzymelinked fluorescent assay (ELFA), using polyclonal antibodies to soybean mosaic virus (SMV), can provide more sensitive levels of detection than those achieved previously by the standard double-sandwich ELISA (HILL and DURAND 1986) and may be equivalent to the recently reported biotin-avidin ELISA (DIACO et al 1985, HILL andDURAND 1986).…”
mentioning
confidence: 99%